PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS KEARIFAN LOKAL MATERI TEKS BERITA BERBANTUAN LIVEWORKSHEETS KELAS XI - Putri Enjel Tarigan; Muhammad Surip (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study was conducted to (1) provide an explanation of the stages of LKPD development to produce a LKPD product Based on Local Wisdom News Text Material Assisted by Liveworksheets for Class XI, (2) describe the feasibility of LKPD to produce a LKPD Based on Local Wisdom News Text Material Assisted by Liveworksheets for Class XI. This study uses the Research and Development (R&D) method with the Borg and Gall model consisting of ten stages, but this study is limited to five stages because it adjusts to limited resources and research scope. The five stages are potential and problem analysis, data collection, product design, product validation, and product revision. This study produced a LKPD Based on Local Wisdom News Text Material Assisted by Liveworksheets for Class XI with material validation results of 78%, media validation of 92%, and Indonesian language teacher assessment of 94%. LKPD obtained an average of 88% (Very Eligible) from the overall validation results in the sense that the LKPD based on local wisdom that was developed was